(untitled) (Revista Ciência Agronômica, 2023)
Extractable phosphorus (P) in soil depends on soil test employed, reactivity of fertilizer and interaction of P added to the soil properties, including organic matter. The aim of this paper was to assess the contents of P extracted from Red Latosol (LVd) and Quartzarenic Neosol (RQ) samples, incubated with 0; 5; 10; 50 or 100 mg kg-1 C-humic acid (C-HA) and 400 mg kg-1 of P, via Araxá phosphate rock (AP), Bayóvar reactive phosphate rock (BP) or single superphosphate (SS). Thus, it was adopted a five (C-HA concentrations) x three (P sources) factorial arrangement, using a randomized block design with three replications. The mixtures of soil, C-HA concentrations and P sources were incubated for 60 days; in sequence, the soil P was extracted by solutions of Bray-1, Mehlich-1 and Mehlich-3 and mixed ion exchange resin. In the LVd and RQ samples, the addition of C-HA reduced extractable phosphorus when the source was AP and BP. The levels of extractable P increased with the application of C-HA in RQ when the source was SS; the average concentration of 50 mg kg-1 C-AH provided the maximum extractable P by Bray-1, Mehlich-3 and mixed resin. The pH is the chemical attribute that most influence the extractable P content of the soil.